2001
DOI: 10.1097/00008390-200110000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A study of infertility treatment and melanoma

Abstract: This study examined the possible association between melanoma and exposure to fertility drugs, specifically clomiphene citrate, human menopausal gonadotrophin (HMG) and human chorionic gonadotrophin (HCG). A cohort of 3186 women who attended a fertility clinic between 1 January 1980 and 31 December 1990 was studied; by January 1996, 14 women had been diagnosed with primary melanoma. Details of fertility treatment were extracted from the clinical records. The incidence of melanoma in the cohort resembled that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 13 publications
0
37
0
1
Order By: Relevance
“…In line with our results, Althuis et al [26] observed no increased risk after use of gonadotrophins and Rossing et al [24] found no increased risk after clomiphene use. However, Althuis et al [26] found an increased risk in women who used clomiphene and remained nulliparous through follow-up and Young et al [27] found a lower risk in clomiphene-users. The analyses by Young et al [27], however, were based on only 14 exposed cases of which six cases were in situ melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with our results, Althuis et al [26] observed no increased risk after use of gonadotrophins and Rossing et al [24] found no increased risk after clomiphene use. However, Althuis et al [26] found an increased risk in women who used clomiphene and remained nulliparous through follow-up and Young et al [27] found a lower risk in clomiphene-users. The analyses by Young et al [27], however, were based on only 14 exposed cases of which six cases were in situ melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Two case-control studies found no significantly increased risk, but were unable to distinguish among different types of fertility drugs [7,25]. Only three cohort studies [24,26,27] have estimated malignant melanoma risk after use of specific types of fertility drugs (clomiphene, gonadotrophins, hMG and hCG) using within cohort analyses. Hence, we can only compare our results to those studies due to the anticipated different effects of different types of fertility drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lediglich bei Frauen mit infertilen Partnern, die mit humanem menopausalen Gonadotropin (HMG) und mit Clomiphen behandelt wurden, trat ein erhöhtes Risiko für ein malignes Melanom auf (OR 3,17, 95%-KI 1,01-9,98). In dieser Arbeit wurde auch der Einfluss der Anzahl Therapiezyklen auf das Melanomrisiko untersucht: So haben Patientinnen mit zwei oder mehr Zyklen HMG (OR 0,23, 95%-KI=0,07-0,84) oder Chlomiphen (OR 0,27, 95%-KI 0,08-0,94) im Vergleich zu Patientinnen mit nur einem oder keinem Zyklus eine signifikant niedrigere Inzidenz für ein malignes Melanom [16]. Diese Daten zeigen eine positive Assoziation zwischen dem Einsatz von Ovulationsinduktoren und malignen Melanomen bei Frauen von infertilen Partnern und eine negative Assoziation bezüglich der niedrigen Dosierung der Substanzen.…”
unclassified